Willingness To Use HIV Self-Testing and Its Association with Sexual Behavior Stigma Among Men Who Have Sex with Men In Padang, Indonesia - Mahathir; Sarah Latifah; Mohd. Djamil; Kiki Hardiansyah Safitri; Bunga Permata Wenny; Siti Yuliharni; Agus Sri Banowo; Devia Putri Lenggogeni; Rika Sarfika; Randy Refnandes; Windy Freska; Fitra Yeni; Winbaktianur; Niko Destri Putra; Ni Ketut Lestari (NERS Jurnal Keperawatan, 2025)
The provision of HIV prevention programs targeting key populations, particularly men who have sex with men (MSM), has been expanding rapidly. HIV self-testing (HIVST) has emerged as an accessible and convenient method for individuals to determine their HIV status independently. However, its utilization remains suboptimal, one potential barrier is the fear of stigma related to sexual behavior experienced by MSM. This study aimed to examine the association between sexual behavior stigma and willingness to undertake HIV self-testing among MSM. A quantitative study with a cross-sectional design was conducted using a non-probability (accidental) sampling technique. The study included 83 MSM participants affiliated with non-profit organization in Padang City. Data collection was carried out from February to May 2025.Two instruments were employed: The Sexual Behavior Stigma (SBS) Scale to assess sexual behavior stigma and a structured questionnaire to measure willingness to perform HIV self-testing. Data were analyzed using Spearman’s rank correlation test. The results showed that the mean score of sexual behavior stigma was 4.15, while the mean score for willingness to undertake HIV self-testing was 0.458, indicating that 45.8% of respondents expressed willingness to perform HIVST. Statistical analysis revealed a significant correlation between sexual behavior stigma and willingness to undertake HIV self-testing (p = 0.000; r = 0.486; r² = 0.236). These findings suggest that higher levels of sexual behavior stigma are associated with lower willingness to perform HIV self-testing. Sexual behavior stigma will lower the success of achieving HIV eradication. It is crucial to reactivate stigma elimination programs to create a safe and supportive environment for MSM as key populations, enabling them to protect themselves from the risk of HIV transmission.